Effectiveness Of Balance Physical Exercise And Muscle Strength About Fall Incident Elderly In Rensing Raya Village, West Sakra District, East Lombok Regency - M Miftahuzzubaidi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Balance exercise is one of the exercises that can be applied to the elderly. This exercise is a physical activity that is done to improve the stability of the body by increasing muscle strength in the legs. Muscle strength is a driving force for movement in completing tasks and can reduce falls especially for the elderly. A fall event is an event reported by a patient or witness, who sees an incident resulting in a person suddenly lying / sitting on the lower floor / place with or without loss of consciousness or injury. This type of research is quantitative, with a Quasi Experimental research design with a Pretest-Posttest Control Group Design approach. The sampling technique used is non probability sampling: purposive sampling with a sample of 34 respondents. data analysis techniques using paired t test. Based on the results of multivariate analysis paired t test on the fall event variable for the treatment group, the results obtained p value 0.006 <0.05. it means that there is a significant effect after being given the treatment of physical exercise balance and muscle strength on the incidence of falls in the elderly. Whereas in the control group, the result was p value 0.018 <0.05. it means that there is a significant effect after being given another treatment, namely gymnastics in the elderly towards the event of falling in the elderly. Balance and muscle strength training is very effective in reducing the number of falls in the elderly. Whereas the control group given elderly exercise also had the effectiveness to reduce the incidence of falls in the elderly. In an effort to reduce the incidence of falls, the elderly can do physical exercise balance and muscle strength regularly